A Micro Computed Tomography Assessment of New Carrier-Based Root Canal Fillings - Raghad A Al-Hashimi (College of Dentistry/ University of Baghdad, 2015)
Background: The main aim of the present study is to qualify and quantify voids formation of root canals obturated with GuttaCore (GC) and experimental Hydroxyapatite polyethylene (HA/PE) as new carrier-based root canal fillings by using micro computed tomography scan. Materials and methods: In the present study, eight straight single-rooted human permanent premolar teeth are selected and disinfected, then stored in distilled water. The teeth decoronated leaving a root length of 12mm each. The root canals instrumented by using crown down technique and the apical diameter of the root canal prepared to a size # 30/0.04 for achieving standardized measurements. A 5mL of 17% EDTA used to remove the smear layer followed by 5mL of 2.5% NaOCl and rinsing with normal saline. Then the shaped root canals were randomly subdivided into two groups of 4 teeth each according to the carrier-based obturation system use, GuttaCore or experimental HA/PE. Afterwards, the obturated roots stored at 37°C with 100% humidity for 72 hours to allow for complete setting of the sealer. Micro-CT was then scanned to quantify the voids within the root canal space. The data were statistically analyzed by one-way ANOVA and post hoc comparison tests (α=0.05). Results: The root canals obturated with both obturation systems, GuttaCore andexperimental HA/PE showed voids formation, particularly at the apical third of the root canal. GC obturation showed a lower percentage of voids volume (1.54%) than the experimental HA/PE obturation (2.3%). The void volume percentage in the GuttaCore system, however, was non-significantly different (P> 0.05) in comparison with the experimental PE/HA system. Conclusions: GuttaCore and experimental HA/PE obturators exhibited voids formation within the entire root canal space. The experimental HA/PE obturator is comparable to the GuttaCore obturator in terms of voids qualification